The evolution of innate immune genes : purifying and balancing selection on β-defensins in waterfowl - Chapman, Joanne R.; Hellgren, Olof; Helin, Anu S.; Kraus, Robert; Cromie, Ruth L.; Waldenström, Jonas (My University, 2016)
In disease dynamics, high immune gene diversity can confer a selective advantage to hosts in the face of a rapidly evolving and diverse pathogen fauna. This is supported empirically for genes involved in pathogen recognition and signalling. In contrast, effector genes involved in pathogen clearance may be more constrained. β-Defensins are innate immune effector genes; their main mode of action is via disruption of microbial membranes. Here, five β-defensin genes were characterized in mallards (Anas platyrhynchos) and other waterfowl; key reservoir species for many zoonotic diseases. All five genes showed remarkably low diversity at the individual-, population-, and species-level. Furthermore, there was widespread sharing of identical alleles across species divides. Thus, specific β-defensin alleles were maintained not only spatially but also over long temporal scales, with many amino acid residues being fixed across all species investigated. Purifying selection to maintain individual, highly efficacious alleles was the primary evolutionary driver of these genes in waterfowl. However, we also found evidence for balancing selection acting on the most recently duplicated β-defensin gene (AvBD3b). For this gene, we found that amino acid replacements were more likely to be radical changes, suggesting that duplication of β-defensin genes allows exploration of wider functional space. Structural conservation to maintain function appears to be crucial for avian β-defensin effector molecules, resulting in low tolerance for new allelic variants. This contrasts with other types of innate immune genes, such as receptor and signalling molecules, where balancing selection to maintain allelic diversity has been shown to be a strong evolutionary force.
Keywords: 570